EXPLORING THE ROLE OF WORKING MEMORY AND COGNITIVE LOAD IN MATHEMATICS LEARNING : A SYSTEMATIC LITERATURE REVIEW - Bayu Romadon; Muhammad Syaifuddin; Reni Dwi Susanti; Anis Farida Jamil; Arif Hidayatul Khsusna (RADJA PUBLIKA, 2026)
This study aims to explore the role of working memory and cognitive load in mathematics learning through a Systematic Literature Review (SLR) approach. This review was conducted to obtain a comprehensive understanding of how working memory capacity and cognitive load management influence mathematical thinking processes, conceptual understanding, and problem-solving performance. The SLR procedure refers to the PRISMA 2020 guidelines, which include the stages of identification, screening, eligibility, and inclusion. Article searches were conducted through the Scopus and Springer Nature Link databases, covering publications from 2015 to 2025. From the articles identified, six met the inclusion criteria and were analyzed thematically. The findings show that visuo-spatial working memory has a significant relationship with mathematical ability, particularly in the development of symbolic representation and problem-solving skills. Additionally, learning effectiveness is strongly influenced by instructional design that manages cognitive load, where strategies such as worked examples, scaffolding, and question-asking have been shown to reduce excessive cognitive load. This review highlights the importance of instructional approaches that consider students’ working memory capacity and cognitive load regulation in order to achieve optimal mathematical understanding.